USE OF BEE POLLENS AS A NUTRITIONAL DIET TO IMPROVE THE QUALITY AND QUANTITY OF SILK PRODUCTION (The Research of Medical Science Review, 2025)
To meet the increasing demand of silk, different research studies have been designed to give silkworms (Bombyx mori L.) (Lepidoptera: Bombycidae) the mulberry leaves fortified with natural and synthetic food additives to increase the production, quality and quantity of silk. The objective of this study was to investigate the effect of bee pollens coated mulberry leaves on the biological and economic parameters of silkworm. Different concentrations of bee pollens (0.5%, 1% and 2%) coated fresh mulberry leaves were given to 5 th instar larvae while unfortified mulberry leaves were fed to control group. The results of the present study showed that there was significant (P˂0.05) increase in the larval weight of treatment group as compared to control group. Highest increase in larval weight (1.047 g ± 0.028) and % ratio of silk gland weight to body weight (30.306 ± 0.430) was observed in the group treated with 1% BP. Furthermore, the cocoon weight, cocoon length and cocoon width was also significantly higher in treatment groups as compared to control group. A comparable pattern was observed in the % shell ratio and % fibroin content. Moreover, the highest cocoon weight (0.654 ± 0.017), cocoon length (31.96 ± 0.217), cocoon width (17.55 ± 0.060), % shell ratio (52.968 ± 2.008) and % fibroin content (76.8 ± 0.335) was found in the group treated with 1% BP. The outcomes of the current experiment have illustrated that silkworm has good adaptability for artificial nutritional diet. By enhancing the protein content in the silkworm feed, the biological and economical parameters of silkworms can be improved. It is conferred from the current study that the use of bee pollens has positive impacts on the productivity of silk.